Pengembangan Sistem Informasi E-Lelang Kendaraan Motor Second Pada FIF Group Kota Bandar Lampung - Sukatmi .; Moch Irvan Maulana Sidiq (STMIK IKMI Cirebon, 2020)
Abstract- FIF group is one of company that moves in financing motor vehicle in the city Bandar Lampung .One of the activities done by FIF group is conducts an auction motor second .To bid process are needed a system information based information technology .The object is to expanding access auction which makes it easy for those interested in to follow auction motor second in FIF group city Bandar Lampung . E-lelang information system second a motor vehicle developed with the methods eXtream program. Used is a design usecase diagram, class diagram and activity diagram. Programming language used to auction development application in adobe dreameweaver, HTML MySQL database support. The end result of development this is a system e-lelang a motor vehicle second in FIF group city Bandar Lampung. With the system e-lelang will ease the FIF in doing bid process and will facilitate the public or company want to join the an auction in the end would increase performance parties FIF group city Bandar Lampung . ABSTRACTadjektiva: abstract, notional, noetic